ENGLISH 3 Geographical and Geo-Strategic Position of Dera Ghazi Khan; : Its Socio-Political and Economic impact on Region History - Najeeb, Romesa; Akhtar, Sohail; Anwar, Abaidullah; Perveen, Sajeela (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2021)
Before the British invasion in Dera Ghazi Khan it was the part of old Derajat and in the colonial era it was the major city of south Punjab. Dera Ghazi Khan was the base of British forward policy towards Balochistan and therefore British administration engaged the Baloch tribes through Tumandari system for their safe passage in Sulaiman range. The paper primarily deals with the geo-strategic position of ancient Dera Ghazi Khan which was considered the important region due to its geographical location as a very important route. Many invaders came to India through this route by crossing the passes of Sulaiman range. The geo-strategic position of Dera Ghazi Khan played a marvelous role in the region as the dead city was located near the west bank of Indus as its eastern boundary while the Mount Sulaiman is still its western boundary. Due to dry weather and hard climatic position the region has its own culture which is under the influence geographical effects of the region. This research paper explores and highlights the significant role of the region in medieval period how the geo-strategic position proved very important in its political geography.